Reconstruction of Carbon Bond Frameworks via Oxapalladacycles Promoted by the Synergistic Effect of Palladium Catalyst and Triethylborane - Ninokata, Ryo; Korogi, Riho; Nakao, Junya; Fukuda, Tsutomu; Onodera, Gen; Kimura, Masanari (Synthesis, 2021)
Pd-catalyzed β-carbon elimination of 3-hydroxy-4-pentenoic acid derivatives promoted by triethylborane proceeds to form conjugated dienes via a decarboxylation process. The formed conjugated dienes undergo the Prins reaction with aldehydes in situ to afford conjugated homoallylic alcohols. These sequential transformations enable the conversion of diastereomeric mixtures of 3-hydroxy-4-pentenoic acids, which are readily prepared from the simple crossed aldol reaction of esters and α,β-unsaturated aldehydes, into 3,5-hexadienyl alcohols with high regio- and stereoselectivities in a single manipulation.
Keywords: palladium; C–C bond cleavage; β-carbon elimination; metallacycles; triethylborane